The Influence of Succession Planning on Organizational Sustainability - Susilo, Susilo; Winarto, Oetami P. (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this study is to analyze how much influence Succession Planning has on Organizational Sustainability through the role of Transformational Leadership, Learning Agility, and Resilience using the SEM-PLS method. This research uses quantitative methods to analyze the influence of Succession Planning on Organizational Sustainability through the roles of Transformational Leadership, Learning Agility, and Resilience. The research used the Structural Equation Modeling (SEM) approach with the Partial Least Squares (PLS) method. Primary research data was obtained by distributing questionnaires to 119 respondents from a total population of 170 employees. The questionnaire contains structured questions that include the variables studied and filled in by respondents online or offline. Data analysis was carried out through descriptive methods using an SEM PLS. The data obtained from the questionnaires were processed and explained statistically by testing the data using SmartPLS 4.0. Based on the results of descriptive analysis and testing through SmartPLS 4.0, it was found that organizational sustainability can be influenced by learning agility and resilience through the mediation of transformational leadership and succession planning. There is a significant relationship between learning agility and resilience variables mediated by transformational leadership and succession planning on organizational sustainability. However, the research results also show that transformational leadership does not have a statistically significant relationship with organizational sustainability, but there is a very significant relationship between transformational leadership and succession planning. The research results are used to establish recommendations to the management of PT XYZ in maintaining the sustainability of the organization and further research.